A Tale of Usurpation and Subversion: SUMO-Dependent Integrity of Promyelocytic Leukemia Nuclear Bodies at the Crossroad of Infection and Immunity - Patra, Upayan; Müller, Stefan (Frontiers in Cell and Developmental Biology, 2021)
Promyelocytic leukemia nuclear bodies (PML NBs) are multi-protein assemblies representing distinct sub-nuclear structures. As phase-separated molecular condensates, PML NBs exhibit liquid droplet-like consistency. A key organizer of assembly and dynamics of PML NBs is the ubiquitin-like SUMO modification system. SUMO is covalently attached to PML and other core components of NBs thereby exhibiting a glue-like function by providing multivalent interactions with proteins containing SUMO interacting motifs (SIMs). PML NBs serve as the catalytic center for nuclear SUMOylation and SUMO-SIM interactions are essential for protein assembly within these structures. Importantly, however, formation of SUMO chains on PML and other NB-associated proteins triggers ubiquitylation and proteasomal degradation coinciding with disruption of NBs. To date, a plethora of nuclear activities such as transcriptional and post-transcriptional regulation of gene expression, apoptosis, senescence, cell cycle, DNA damage response, and DNA replication have been associated with PML NBs. Not surprisingly, therefore, SUMO-dependent PML NB integrity has been implicated in regulating many physiological processes including tumor suppression, metabolism, drug-resistance, development, cellular stemness, and anti-pathogen immune response. The interplay between PML NBs and viral infection is multifaceted. As a part of the antiviral determinants, constituents of PML NBs are crucial restriction factors for many viruses and a mutual positive correlation has been found to exist between PML NBs and the interferon response. Viruses, in turn, have developed counterstrategies for disarming PML NB associated immune defense measures. On the other end of the spectrum, certain viruses are known to usurp specific PML NB components for successful replication and disruption of these sub-nuclear foci was recently linked to the stimulation rather than curtailment of antiviral gene repertoire. Importantly, the ability of invading virions to manipulate the host SUMO modification machinery is essential for this interplay between PML NB integrity and viruses. Moreover, compelling evidence is emerging in favour of bacterial pathogens to negotiate with the SUMO system thereby modulating PML NB-directed intrinsic and innate immunity. In the current context, we will present an updated account of the dynamic intricacies between cellular PML NBs as the nuclear SUMO modification hotspots and immune regulatory mechanisms in response to viral and bacterial pathogens.